Infidelity's aftermath: Appraisals, mental health, and health-compromising behaviors following a partner's infidelity. (September 2018) - Shrout, M. Rosie; Weigel, Daniel J.
Guided by transactional stress theory, this research investigated the role of appraisals in noninvolved partners' mental health and health-compromising behaviors after infidelity. Responses from 232 college students who were recently cheated on revealed that negative appraisals (partner blame, self-blame, and causal attribution) had indirect effects on health-compromising behaviors through mental health (depression, anxiety, and distress). Moderated mediation analyses revealed that gender altered the indirect effect of partner and self-blame on health-compromising behaviors through mental health. Men's health-compromising behaviors did not differ based on their appraisals or mental health. However, women who reported negative appraisals and high levels of mental health consequences engaged in more health-compromising behaviors. These findings suggest that perceptions of a partner's infidelity are important, and that those perceptions affect noninvolved partners' mental health and physical health behaviors.